2006
DOI: 10.2527/jas.2006-144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a single nucleotide polymorphism of the insulin-like growth factor binding protein 2 gene and its association with growth and body composition traits in the chicken

Abstract: Insulin-like growth factor binding protein 2 regulates a broad spectrum of biological activities involved in growth, development, and differentiation. The current study was designed to investigate the associations of IGFBP2 gene polymorphisms with chicken growth and body composition traits. The Northeast Agricultural University Resource Population (NEAURP) was established by crossing broiler sires, derived from lines at Northeast Agricultural University, that were divergently selected for abdominal fat, with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 16 publications
2
42
2
Order By: Relevance
“…The plausible reason for this may be that genetic drift, selection and other factors may affect the allele frequency. These SNPs had significant effect on hatch weight, body weight at 8 weeks of age, egg weight at 300 days and body weight at 300 days which have difference with the aforementioned results (Leng et al, 2009;Li et al, 2006). STAT5b is the important modulator of the growth hormone, growth hormone receptor, IGF, prolactin and insulin signaling pathways.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…The plausible reason for this may be that genetic drift, selection and other factors may affect the allele frequency. These SNPs had significant effect on hatch weight, body weight at 8 weeks of age, egg weight at 300 days and body weight at 300 days which have difference with the aforementioned results (Leng et al, 2009;Li et al, 2006). STAT5b is the important modulator of the growth hormone, growth hormone receptor, IGF, prolactin and insulin signaling pathways.…”
Section: Discussioncontrasting
confidence: 37%
“…In chickens, Leng et al (2009) detected one SNP (C1996A) of the IGFBP-2 gene was associated with abdominal fat weight and percentage of abdominal fat. Li et al (2006) detected a C/T SNP of the IGFBP-2 gene which had effect on BW, metatarsus length, shank length, femur length, shank weight, femur weight, metatarsus claw weight and abdominal fat weight of chicken. DeKoning et al (2003) reported that a QTL for carcass weight was mapped between marker brackets MCW0030 and MCW0236 (about 2.3 to 29 Mb) on GGA7, a region that contains chicken IGFBP2 gene (23 to 24 Mb).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IGF-I gene had no effect on egg production of domestic chickens, despite its great contribution in stimulating growth, protein synthesis, cell proliferation and differentiation, egg development (McMurtry et al, 1997;Yun et al, 2005;Li et al, 2006;) and IGF-I/PstI has been proven to have correlation with egg production and days of continuous egglaying (Kim et al, 2004;Li et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…These traits are under complex genetic controls; and molecular markers for growth may contribute to more efficient selection for these traits (Li et al, 2006). Marker-assisted selection may increase selection efficiency and improve production performance.…”
Section: Introductionmentioning
confidence: 99%